Prophylactic Effects of Ivermectin and Closantel Treatment in the Control of Oestrus ovis Infestation in Sheep - Bello, Hornblenda Joaquina Silva; Lins, José Gabriel Gonçalves; Albuquerque, Ana Cláudia Alexandre de; Ferreira, Gabriel Badial; Amarante, Mônica Regina Vendrame; Amarante, Alessandro Francisco Talamini do (Frontiers in Veterinary Science, 2022)
The sheep nasal bots Oestrus ovis is parasite of the nasal cavities and sinuses of small ruminants causing oestrosis, one of the most frequent parasitic diseases in sheep and goats. The widely use of ivermectin and closantel by the sheep breeders in the treatment and prophylaxis of gastrointestinal nematodes resulted in widespread cases of anthelmintic resistance. However, there is no report about cases of O. ovis with drug-resistance. In this study, we evaluated the prophylactics and therapeutic effects of both antiparasitics in sheep with O. ovis natural infestation. The trial was carried out from early December 2019 to March 2020, with 30 crossbred males lambs allocated into three groups of 10 animals each: control (without treatment), treated with ivermectin (0.2 mg/kg subcutaneously) and treated with closantel (10 mg/kg orally). The animals were kept together grazing the same pasture area. The treatment groups were drenched in two occasions 70 days apart: on 5th December 2019 and on 13th February 2020. On 19th March 2020, all lambs were slaughtered. The lamb heads were removed and sectioned along their longitudinal and sagittal axis to search for larvae. Recovered O. ovis larvae were counted and identified according to their developmental stage (L1, L2 and L3). Seven of the control lambs were infested with O. ovis larvae ranging from six to 17 larvae (11.6 mean infestation intensity). All recovered larvae from control group were intact and active. Three animals treated with ivermectin had O. ovis larvae (1 to 3 larvae), however they were dead and in degeneration. The animals treated with closantel did not have any larvae. The clinical suggestive signs of oestrosis were scarce over the experimental period. The averages of daily weight gain were similar (p> 0.05) among groups. Closantel and ivermectin had high efficacy against oestrosis and O. ovis parasitism did not hinder the performance of lambs.